The Influence of Company Size and Capital Structure on Earnings Quality in Manufacturing Companies in the Food & Beverage Sub-Sector Listed on the Indonesia Stock Exchange (BEI) - Ika Nurhaliza; Geby Citra Ananda; Vira Dwi Ananda; Nia Deniati Lumbangaol; Ayu Pebrianti (International Forum of Researchers and Lecturers, 2022)
This study aims to determine the size of the company, and capital structure, on the quality of earnings. The sample in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. Data was collected by the documentation method. The sample selection used a purposive sampling method and obtained 17 companies. Hypothesis testing was carried out using pooled least s-quare data regression analysis method. The results of this study indicate: (1) Firm Size has a positive and significant effect on Earnings Quality and (2) Capital Structure has a negative and insignificant effect on Earnings Quality. by 45% influenced by other factors not described in this study.